THE EFFECT OF EVIDENCE OF SERVICE ON CUSTOMER SATISFACTION IN GRAND HOTEL LEMBANG - Andhi Sukma; Mohd Haizam Saudi; Obsatar Sinaga (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The hospitality service industry has experienced an increase, but especially for companies engaged in services, the intangibles of services are considered to have made service providers make strategies to make the services / services provided to their customers visible, so the strategy to market tangible products is different from marketing services. Grand Hotel Lembang is one of the 3-star hotels, it is considered necessary to find out how the perception of guests staying about the implementation of the Evidence of Service applied in the hotel in an effort to provide the best service for its guests. Based on this background it is interesting to study further about how much the relationship and the influence of Evidence of Service on the satisfaction of customers who stay at the Grand Hotel Lembang. This research is using multiple regression analysis of 200 respondents. The results show that Grand Hotel Lembang customer satisfaction is influenced by Evidence of Service by 44%, where the process dimension has the greatest influence between the dimensions of people and physical evidence. This shows that the other 56% is influenced by other factors outside of Evidence of Service, so Grand Hotel Lembang should have special features (uniqueness) in addition to trying to make continuous improvements in order to get new customers without ignoring existing customers.